A Technological Review on Fast Chargers for Electric Vehicles: Standards, Architectures, Power Converter Topologies, Fast Charging Techniques, Impacts and Future Research Directions - Seleem, Mohamed; Atia, Yousry; Abou-Zalam, Belal; Abd-Elhaleem, Sameh (Association for Scientific Computing Electronics and Engineering (ASCEE), 2024)
Within a universe in which concerns about petroleum resources depletion and ecological issues are increasing, the technological evolution of electric mobility has quickened to overcome these concerns. Vehicle electrification technology is seen as a promising and viable substitute for prospective transport systems. Electric vehicles (EVs) offer a solution for reducing the reliance on fossil fuels, improving air quality, integrating easily with renewable energies, and enhancing energy efficiency, especially when smart grids have become omnipresent. However, range anxiety and long charging times remain substantial barriers to the extensive embrace of these vehicles, impeding a seamless shift from conventional vehicles to EVs. Reducing EV recharging time is considered a pivotal element in promoting consumer interest and increasing their market appeal. Thus, EV commercial deployment relies heavily on the presence of an adequate fast-charging infrastructure. Fast-charging infrastructure will decrease drivers' wait times for vehicle charging, providing a refueling experience like that of gasoline vehicles. Hence, a significant portion of research efforts have been dedicated to the advancement of fast chargers (FCs) designed to rapidly recharge EV batteries. It is crucial to opt for the appropriate power electronic interfaces for these chargers to avoid possible grid-related issues and improve overall system efficiency. This review is concentrated on presenting pertinent information regarding EV FCs, including various standards, architectures, power converter topologies, compatible battery chemistries, and fast-charging techniques. Finally, the significant impacts of the integration of fast-charging with both the AC grid and traction batteries are presented in detail.